If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 9) = 39 Reorder the terms: 3(9 + 2x) = 39 (9 * 3 + 2x * 3) = 39 (27 + 6x) = 39 Solving 27 + 6x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 6x = 39 + -27 Combine like terms: 27 + -27 = 0 0 + 6x = 39 + -27 6x = 39 + -27 Combine like terms: 39 + -27 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 50-2x+7-3x=12 | | 18-2v=v+3 | | 4(3t-9)=3(4t-12) | | 4x+8=21 | | 6m+2n-2m+9m= | | 15=6v+7 | | 2a+3b=20 | | (n-5)(n+5)=28 | | 4x^2-21x+31=3x+4 | | -30-6x=6-10x | | 8c-1=6c-5 | | 147-4x=6x+17 | | 5u+7=20-8u | | 6x^2+13x-8=0 | | 81-3x=8x+15 | | 71-4x=9x+19 | | 3x^2=12 | | 6x+8=78-4x | | 2x+13=93-6x | | 4x^2-18x+61=0 | | 7b+10=4b+1 | | 9+7x=81+x | | 10+8x=-2x+34 | | 5x-5=14x-32 | | 11x+21=3x+133 | | 49x^2-81=0 | | 6x+18=16x-92 | | 6X+14=113-5x | | 4a+6=2a+2 | | -17-2x=8-7x | | 12+2x=5x | | 5(x-6)=-28.5 |